Biodegradable polyester composition as well as preparation method and application thereof
By optimizing the proportion of components of biodegradable polyester, starch and polyhydroxy alcohols, and improving the transparency and mechanical properties of high-starch-based biodegradable films, the problems of insufficient transparency and poor mechanical properties of films in the prior art are solved, and the problem of insufficient film transparency and poor mechanical properties in the prior art is realized. The practical application requirements of high-starch-based films.
Patent Information
- Application Number
- CN202411571930.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-10
AI Technical Summary
In practical applications, biodegradable films with high starch content have problems such as insufficient transparency, low impact strength and poor thermal performance.
Using a biodegradable polyester composition, including a specific proportion of biodegradable polyester, starch and polyhydroxy alcohol, the component ratio is optimized through indicators such as nuclear magnetic resonance hydrogen spectrum and dynamic light scattering multimodal particle size ratio, and the combination is improved. The compatibility and water absorption of the substances can reduce the light refractive index and diffuse reflection degree, thereby improving the transparency and mechanical properties of the film.
It has achieved high transparency, excellent mechanical properties and good thermal performance of high starch-based biodegradable films, meeting the practical application needs of thicknesses of 12μm or above.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer engineering plastics, and in particular relates to a biodegradable polyester composition and a preparation method and application thereof. Background Art
[0002] As a key project of green and sustainable energy development, bio-based materials have received great attention from the country and industry leaders. With the successive victories in scientific research, bio-based products will surely play a greater role in the future.
[0003] Increasing bio-based content by adding macromolecular materials from natural sources such as starch is an important means to reduce costs and carbon emissions, but starch filling, especially high starch filling (based on the product, the mass percentage of starch ≥15% is high starch filling) brings great challenges to product performance and processing technology. High-starch-based biodegradable films have the advantages of low cost, high bio-based content, and home compostability, and have always been favored by the market. However, in the existing technology, high-starch-content films have insufficient transparency in the actual application thickness (thickness ≥12μm) of fruit and vegetable bags, supermarket shopping bags, etc., which brings troubles in content identification and pricing, and has application defects; at the same time, there are also problems such as low impact strength and poor heat sealing performance. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a biodegradable polyester composition having high transparency and excellent mechanical properties when used in the preparation of film products, as well as a preparation method and application thereof.
[0005] To achieve the above object, in a first aspect of the present invention, the present invention provides a biodegradable polyester composition, wherein the biodegradable polyester composition comprises the following components in parts by weight:
[0006] 13-88 parts of biodegradable polyester, 13-88 parts of starch, 2-42 parts of polyhydroxy alcohol;
[0007] The ratio R of the integral value J1 of the proton signal between 5.0-5.3 ppm and the integral value J2 of the proton signal between 8.0-8.2 ppm on the nuclear magnetic resonance hydrogen spectrum of the biodegradable polyester J 0.05-0.35;
[0008] The ratio R of the dynamic light scattering multi-peak particle size D50 value D1 measured after the starch is dispersed in water as a solvent to the D50 value D2 measured after the starch is dispersed in ethanol as a solvent D ≥1.3;
[0009] The functionality of the polyhydric alcohol is ≥2;
[0010] The mass ratio of the biodegradable polyester to the starch is ≥1.
[0011] The biodegradable polyester composition provided by the present invention can avoid the problem of easy occurrence of gaps between the continuous phase and the dispersed phase due to the difference in thermal expansion and contraction rates of high starch content by selecting components in appropriate mass fractions in the subsequent preparation process, even when preparing a high-starch-based biodegradable film (mass percentage of starch ≥15%). That is, the technical solution provided by the present invention is conducive to the compatibility between the two phases, thereby reducing the light refractive index and diffuse reflection degree of the composition, thereby improving the transparency of the film product prepared subsequently. Even when the thickness of the film product prepared subsequently is 12 μm or more, the transparency of the obtained product can still meet practical applications; and the reasonable combination of the components can also effectively improve the mechanical properties of the composition, specifically, the tensile strength, dart impact strength and heat sealing performance of the obtained product are all high.
[0012] Specifically, the ratio R of the integral value J1 of the proton signal between 5.0-5.3 ppm and the integral value J2 of the proton signal between 8.0-8.2 ppm on the hydrogen nuclear magnetic resonance spectrum of the biodegradable polyester is J The ratio of 0.05-0.35 indicates that the ratio of aliphatic polyester to aliphatic-aromatic copolyester in biodegradable polyester is appropriate, which can effectively D The starch and polyhydroxy alcohol with a certain value interact with each other to improve the compatibility between the components and avoid the problem of increased gap ratio between the dispersed phase and the continuous phase due to the difference in thermal expansion and contraction rates caused by the introduction of more starch during the preparation process; at the same time, the ratio of the D50 value D1 of starch dispersed with water as solvent to the D50 value D2 of starch dispersed with ethanol as solvent is R D ≥1.3 can have a greater equilibrium water absorption rate and further reduce the gap ratio between the two phases; thereby improving the transparency, mechanical properties and heat-sealing properties of the film product prepared using the composition.
[0013] It should be noted that the spectrum of the biodegradable polyester composition on the nuclear magnetic resonance hydrogen spectrum is a 5 mg / mL test solution prepared with deuterated chloroform as a solvent, and is tested using an Ascend 600 nuclear magnetic resonance spectrometer. The test temperature is 25°C, and the deuterated reagent adds TMS (tetramethylsilane) as an internal standard. The number of scans is 32 times. The spectrum is then automatically integrated using MestReNova software to calculate the ratio of J1 to J2, thereby obtaining R J Value range.
[0014] For example, the R JIt can be any point value or any two point range value between 0.05-0.35, for example, it can be 0.10-0.30, 0.1-0.15, etc., or it can be 0.05, 0.07, 0.09, 0.10, 0.12, 0.14, 0.16, 0.18, 0.20, 0.22, 0.24, 0.26, 0.28, 0.30, 0.32, 0.34, 0.35, etc.
[0015] It should be noted that the dynamic light scattering multi-modal particle size D50 obtained by the test in the present invention refers to Dv50. The starch in the biodegradable polyester composition is obtained by dissolving the biodegradable polyester composition with dichloromethane, then centrifuging, collecting the precipitate and washing it with dichloromethane to obtain starch. Then, the starch is dispersed with water or ethanol as solvent and tested; the test method for the D50 value of starch dispersed with water as solvent is as follows: take 1g of starch and use 100mL of deionized water as the dispersed phase, stir for 5min, test the multi-modal particle size D50 value on a Mastersizer laser particle size analyzer, and record it; the test method for the D50 value of starch dispersed with ethanol as solvent is as follows: take 1g of starch and use 100mL of ethanol as the dispersed phase, stir for 5min, test the multi-modal particle size D50 value on a Mastersizer laser particle size analyzer, and record it; then calculate the ratio R of the D50 value D1 of starch dispersed with water as solvent to the D50 value D2 of starch dispersed with ethanol as solvent D .
[0016] For example, the R D The value may be any point value or any range of two points between ≥1.3, for example, it may be 1.3-1.8, or it may be 1.30, 1.35, 1.40, 1.45, 1.50, 1.55, 1.60, 1.65, 1.70, 1.75, 1.80, etc.
[0017] It should be noted that the dynamic light scattering multi-peak particle size D50 value D1≤50nm measured after the starch is dispersed in water as solvent, and the D50 value D2≤40nm measured after the starch is dispersed in ethanol as solvent.
[0018] Exemplarily, the mass ratio of the biodegradable polyester to starch can be any point value ≥1 or any two-point range value, such as 1-2.5, 1-1.6, 1-2, etc., or can be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, etc.
[0019] Preferably, the ratio R of the integral value J1 of the proton signal between 5.0-5.3 ppm and the integral value J2 of the proton signal between 8.0-8.2 ppm on the hydrogen nuclear magnetic resonance spectrum of the biodegradable polyester is J It is 0.1-0.15.
[0020] In the biodegradable polyester composition, the mass percentage of starch is 15-50%.
[0021] For example, the biodegradable polyester may be any point value or any two point range value between 13-88 parts, such as 15-85 parts, or 13 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 88 parts, etc.; the starch may be any point value or any two point range value between 13-88 parts, such as 15-85 parts, or 13 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 88 parts, etc. The polyhydric alcohol can be any point value or any two point range value between 2-42 parts, for example, it can be 3-41 parts, or it can be 2 parts, 4 parts, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, 42 parts, etc.
[0022] As a preferred embodiment of the biodegradable polyester composition of the present invention, the biodegradable polyester composition comprises the following components in parts by weight: 50-80 parts of biodegradable polyester, 20-50 parts of starch, and 10-20 parts of polyhydroxy alcohol.
[0023] The present invention has been found that the added mass parts of the components will affect the performance of the product. When the mass parts of the components are further selected to be within the above range, the comprehensive effect of the obtained product is more excellent.
[0024] As a preferred embodiment of the biodegradable polyester composition of the present invention, the ratio of the D50 value D1 of the starch dispersed with water as solvent to the D50 value D2 of the starch dispersed with ethanol as solvent is R D It is 1.30-1.50.
[0025] The present invention has found that the ratio of the D50 value D1 of starch dispersed with water as solvent to the D50 value D2 of starch dispersed with ethanol as solvent is R D To a certain extent, it reflects the equilibrium water absorption rate of starch, and R D The value will also affect the shear dispersibility of starch during the preparation process; when further selecting R D When the molecular weight of the film product is 1.30-1.50, when the obtained composition is used in the preparation of a film product, the obtained film product has higher transparency, and higher tensile strength, dart impact strength and heat sealing performance.
[0026] For example, the R D The value can be any point value or any two point range value between 1.30-1.50, for example, it can be 1.30, 1.31, 1.32, 1.33, 1.34, 1.35, 1.36, 1.37, 1.38, 1.39, 1.40, 1.41, 1.42, 1.43, 1.44, 1.45, 1.46, 1.47, 1.48, 1.49, 1.50, etc.
[0027] As a preferred embodiment of the biodegradable polyester composition of the present invention, the functionality of the polyhydric alcohol is 3-6.
[0028] The present invention has found that the hydroxyl groups in the polyhydric alcohol will affect the compatibility between the biodegradable polyester and the starch, thereby affecting the comprehensive performance of the product. When the functionality of the polyhydric alcohol is further selected to be 3-6, the comprehensive performance of the obtained product is better.
[0029] For example, the functionality of the polyhydric alcohol may be any point value or any two point range value between 3 and 6, such as 3, 4, 5, 6, etc.
[0030] As a preferred embodiment of the biodegradable polyester composition of the present invention, the polyhydric alcohol includes at least one of glycerol, diglycerol, triglycerol, tetraglycerol and sorbitol.
[0031] As a preferred embodiment of the biodegradable polyester composition of the present invention, the biodegradable polyester includes aliphatic polyester and aliphatic-aromatic copolyester.
[0032] As a preferred embodiment of the biodegradable polyester composition of the present invention, the aliphatic-aromatic copolyester comprises a copolyester formed by condensation of at least one aromatic dibasic acid selected from terephthalic acid and furandicarboxylic acid, at least one aliphatic dibasic acid selected from adipic acid, succinic acid, azelaic acid, sebacic acid and brassylic acid, and at least one diol selected from propylene glycol and butanediol.
[0033] The present invention has no special requirements for the molar ratio of aromatic dibasic acid to aliphatic dibasic acid in aliphatic-aromatic copolyester, and the purpose of the present invention can be achieved within the range of 0.5-2. The present invention has no special requirements for the melt flow rate of aliphatic-aromatic copolyester, and the purpose of the present invention can be achieved within the range of 1-20g / 10min; wherein, the melt flow rate test method of aliphatic-aromatic copolyester is GB / T 3682-2000, and the test conditions are 190°C and 2.16kg.
[0034] The present invention has found that the type of biodegradable polyester will also affect the performance of the product. When the biodegradable polyester includes aliphatic polyester and aliphatic-aromatic copolyester, especially a further selected aliphatic-aromatic copolyester, which is a copolyester formed by condensation of at least one aromatic dibasic acid selected from terephthalic acid and furandicarboxylic acid, at least one aliphatic dibasic acid selected from adipic acid, succinic acid, azelaic acid, sebacic acid, and brassylic acid, and at least one diol selected from propylene glycol and butanediol, the obtained product has higher transparency and better mechanical properties.
[0035] As a preferred embodiment of the biodegradable polyester composition of the present invention, the aliphatic polyester comprises polylactic acid, and the aliphatic polyester has a dextrorotatory monomer content of 1-15%.
[0036] Preferably, the aliphatic polyester has a dextrorotatory monomer content of 6-15%.
[0037] The present invention has found that when the right-handed monomer content of the aliphatic polyester is further selected to be 6-15%, the compatibility between the components is better, and the gap ratio between the dispersed phase and the continuous phase during the preparation process is lower, which can effectively reduce the light refractive index and diffuse reflection degree of the film product prepared subsequently, improve the transparency of the film product, and the excellent compatibility between the components can also improve the mechanical properties and heat sealing properties of the prepared product.
[0038] Exemplarily, the dextrorotatory monomer content of the aliphatic polyester can be any point value or any two point range values between 6-15%, such as 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc.
[0039] The present invention has no special requirements for the weight average molecular weight of polylactic acid, and the purpose of the present invention can be achieved within the range of 30,000-120,000; wherein the weight average molecular weight of polylactic acid is measured according to the YY / T 1678-2019 standard method.
[0040] As a preferred embodiment of the biodegradable polyester composition of the present invention, the starch includes at least one of natural starch and natural starch derivatives.
[0041] Exemplarily, the natural starch includes at least one of corn starch, potato starch, rice starch, and cassava starch; the natural starch derivative includes at least one of an ester of natural starch, an ether of natural starch, and an oxide of natural starch.
[0042] It should be noted that, without affecting the effect of the biodegradable polyester composition of the present invention, additives such as antioxidants, antistatic agents, weathering agents, lubricants, anti-blocking agents, colorants, etc. may be added as needed.
[0043] In the second aspect of the present invention, the present invention provides a method for preparing a biodegradable polyester composition, the preparation method comprising the following steps: weighing the dried raw materials, mixing them and feeding them into a twin-screw extruder, extruding, drawing, cooling, pelletizing and drying to obtain the biodegradable polyester composition.
[0044] As a preferred embodiment of the preparation method of the present invention, in the extrusion, the screw aspect ratio is 40:1, and the set temperature is: zone 1: 60-90°C, zone 2: 100-130°C, zone 3: 140-170°C, zone 4: 150-190°C, zone 5: 150-190°C, zone 6: 150-190°C, zone 7: 150-190°C, zone 8: 150-190°C, zone 9: 150-190°C, die head: 150-190°C, screw speed: 250-350rpm, extrusion speed: 400-600kg / h.
[0045] In the third aspect of the present invention, the present invention provides use of the biodegradable polyester composition in preparing a biodegradable film product.
[0046] Exemplarily, the biodegradable film product includes any one of a shopping bag, a kitchen waste bag, a food packaging film, and an agricultural mulch film.
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] In the biodegradable polyester composition provided by the present invention, the ratio R of the integral value J1 of the proton signal between 5.0-5.3 ppm and the integral value J2 of the proton signal between 8.0-8.2 ppm on the nuclear magnetic resonance hydrogen spectrum is used. J Ratio of D50 value D1 of biodegradable polyester dispersed in water as solvent to D50 value D2 of biodegradable polyester dispersed in ethanol as solvent within a specific range D The starch and polyhydroxy alcohol within a specific range work together within a given mass range to effectively improve the transparency and mechanical properties of the biodegradable polyester composition. In addition, the preparation method of the biodegradable polyester composition provided by the present invention is simple to operate and is conducive to practical application. DETAILED DESCRIPTION
[0049] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0050] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0051] Aliphatic polyester 1: polylactic acid, right-handed monomer content 8%, KB600 NF50, Zhuhai Jinfa Biomaterials Co., Ltd.
[0052] Aliphatic polyester 2: polylactic acid, 1% dextrorotatory monomer content, KB600 NF10, Zhuhai Jinfa Biomaterials Co., Ltd.
[0053] Aliphatic-aromatic copolyester 1: polybutylene terephthalate-adipate, KB100, Zhuhai Jinfa Biomaterial Co., Ltd.;
[0054] Aliphatic-aromatic copolyester 2: polybutylene terephthalate-sebacate, A300, Zhuhai Jinfa Biomaterial Co., Ltd.;
[0055] Biodegradable Polyester 1:R J is 0.15, a mixture of aliphatic polyester 1 and aliphatic-aromatic copolyester 1 in a ratio of 1:10;
[0056] Biodegradable Polyester 2:R J is 0.1, a mixture of aliphatic polyester 1 and aliphatic-aromatic copolyester 1 in a ratio of 1:14.7;
[0057] Biodegradable polyester 3:R J is 0.05, a mixture of aliphatic polyester 1 and aliphatic-aromatic copolyester 1 in a ratio of 1:32.3;
[0058] Biodegradable polyester 4:R J is 0.35, a mixture of aliphatic polyester 1 and aliphatic-aromatic copolyester 1 in a ratio of 1:4;
[0059] Biodegradable polyester 5:R J is 0.15, a mixture of aliphatic polyester 2 and aliphatic-aromatic copolyester 1 in a ratio of 1:10;
[0060] Biodegradable polyester 6:R J is 0.15, a mixture of aliphatic polyester 1 and aliphatic-aromatic copolyester 2 in a ratio of 1:10;
[0061] Biodegradable polyester 7:R J is 0.01, a mixture of aliphatic polyester 1 and aliphatic-aromatic copolyester 1 in a ratio of 1:109;
[0062] Biodegradable polyester 8:R J is 0.4, a mixture of aliphatic polyester 1 and aliphatic-aromatic copolyester 1 in a ratio of 1:2.9;
[0063] Starch 1: BENEFORM 2260, Ingredion, USA;
[0064] Starch 2: BENEFORM 2160, Ingredion, USA;
[0065] Starch 3: corn starch, Shandong Shouguang Juneng Golden Corn Development Co., Ltd.;
[0066] Starch 4: ZYT-201, Hangzhou Zhiyou Technology Co., Ltd.;
[0067] Starch 5: potato starch, Guyuan County Baishunyuan Starch Co., Ltd.
[0068] Polyhydric alcohol 1: glycerol, functionality 3, commercially available;
[0069] Polyhydric alcohol 2: sorbitol, functionality 6, commercially available;
[0070] Polyhydric alcohol 3: ethylene glycol, functionality 2, commercially available;
[0071] Polyhydric alcohol 4: pentaglycerol, functionality 7, commercially available.
[0072] Examples 1-15 and Comparative Examples 1-5
[0073] The present invention provides a biodegradable polyester composition according to the embodiments and comparative examples. The components (parts by weight) of the biodegradable polyester composition are shown in Table 1-2, wherein R D The ratio R of the D50 value D1 of the starch dispersed in water as solvent to the D50 value D2 of the starch dispersed in ethanol as solvent is measured after the starch is separated from the biodegradable polyester composition prepared in the corresponding embodiment and comparative example. D ;
[0074] Table 1
[0075]
[0076] Table 2
[0077]
[0078]
[0079] The method for preparing the biodegradable polyester composition provided in Example 1 comprises the following steps:
[0080] The biodegradable polyester is first dried in an oven at 80° C. for 5 hours, then mixed with starch and polyhydroxy alcohol in a high-speed mixer for 3 minutes, and the resulting uniform mixture is fed into a twin-screw extruder for melt plasticization, extrusion, and granulation to obtain a biodegradable polyester composition; the twin-screw extruder is a co-rotating parallel twin-screw extruder, the screw aspect ratio is 40:1, and the set temperature is: zone 1: 80° C., zone 2: 110° C., zone 3: 150° C., zone 4: 180° C., zone 5: 180° C., zone 6: 180° C., zone 7: 180° C., zone 8: 180° C., zone 9: 180° C., die head: 180° C., screw speed: 300 rpm, extrusion speed: 500 kg / h;
[0081] The preparation methods of the biodegradable polyester compositions provided in Examples 2-15 and Comparative Examples 1-5 are consistent with that in Example 1, except that no related components are added.
[0082] Effect example
[0083] The effect example of the present invention verifies the performance of the biodegradable polyester composition prepared in Examples 1-15 and Comparative Examples 1-5. The biodegradable polyester composition prepared in the Examples and Comparative Examples is made into a film on a single screw film blowing machine with a screw diameter of 45 cm and an aspect ratio of 20:1. Specifically, a thickness card table is used to control the same apparent thickness. According to the ISO 4593-1993 standard test, the average apparent thickness is 12 μm; then the prepared film is subjected to a performance test, including the following aspects:
[0084] 1) Transparency test: Cut the film into samples with a diameter of 7 cm, stabilize them in a humidity environment of 23±3℃ and 50±5RH% for 1 hour, and then test their transmittance and haze values using a Shanghai Shenguang WGT-S transmittance and haze tester. The test was repeated 3 times in parallel, and the average value was taken to obtain the transmittance and haze values.
[0085] 2) Tensile strength: Test according to GB / T 1040.3-2006 standard method, the test speed is (500±50) mm / min, and the transverse tensile strength and longitudinal tensile strength of the film are recorded;
[0086] 3) Dart impact strength: tested in accordance with GB / T 9639.1-2008 standard method;
[0087] 4) Heat seal strength: Tested in accordance with QB / T 2358-1998 standard method, with a test speed of (300±50) mm / min.
[0088] The results obtained are shown in Table 3;
[0089] Table 3
[0090]
[0091] It can be seen from Table 3 that when the technical solution of the present invention is adopted, the film formed by the prepared biodegradable polyester composition has excellent transparency and mechanical properties. Specifically, when the film with an average apparent thickness of 12 μm prepared by the biodegradable polyester composition has a light transmittance of more than 86%, a haze of less than 45%, a longitudinal tensile strength of more than 20 MPa, a transverse tensile strength of more than 16 MPa, a dart impact strength of more than 165 g, and a heat sealing strength of more than 15 N / 15 mm;
[0092] It can be seen from Example 1, Examples 5-9 and Comparative Examples 1-2 that the selection of biodegradable polyester will affect the comprehensive performance of the product. When the parameters of the biodegradable polyester are further selected within the range given in the present invention, the comprehensive effect of the obtained product is excellent; when the parameters of the biodegradable polyester in Comparative Examples 1-2 are not within the range of the present invention, the mechanical properties of the obtained product are significantly reduced;
[0093] It can also be seen from Examples 1-4 and Comparative Example 3 that the weight of the components also has a great influence. When the weight of starch in Comparative Example 3 is greater than that of the biodegradable polyester, the mechanical properties of the obtained product decrease significantly and the light transmittance also decreases.
[0094] It can be seen from Example 1, Examples 10-12 and Comparative Example 4 that the selection of starch will also affect the performance of the product. When the parameters of the starch in Comparative Example 4 are not within the scope of the present invention, the comprehensive performance of the obtained product is significantly reduced. It can be seen from Example 1, Examples 13-15 and Comparative Example 5 that when the hydroxyl degree of the alcohol substance selected in Comparative Example 5 is not within the scope of the present invention, the obtained product cannot meet the requirements.
[0095] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A biodegradable polyester composition, characterized in that The biodegradable polyester composition comprises the following components in parts by weight: 13-88 parts of biodegradable polyester, 13-88 parts of starch, 2-42 parts of polyhydroxy alcohol; The ratio R of the integral value J1 of the proton signal between 5.0-5.3 ppm and the integral value J2 of the proton signal between 8.0-8.2 ppm on the nuclear magnetic resonance hydrogen spectrum of the biodegradable polyester is J 0.05-0.35; The ratio R of the dynamic light scattering multi-peak particle size D50 value D1 measured after the starch is dispersed in water as a solvent to the D50 value D2 measured after the starch is dispersed in ethanol as a solvent D ≥1.3; The functionality of the polyhydric alcohol is ≥2; The mass ratio of the biodegradable polyester to the starch is ≥1.
2. The biodegradable polyester composition according to claim 1, characterized in that The biodegradable polyester composition comprises the following components in parts by weight: 50-80 parts of biodegradable polyester, 20-50 parts of starch, and 10-20 parts of polyhydroxy alcohol.
3. The biodegradable polyester composition according to claim 1, characterized in that The ratio R of the dynamic light scattering multi-peak particle size D50 value D1 measured after the starch is dispersed in water as a solvent to the D50 value D2 measured after the starch is dispersed in ethanol as a solvent D It is 1.30-1.
50.
4. The biodegradable polyester composition according to claim 1, characterized in that The functionality of the polyhydric alcohol is 3-6.
5. The biodegradable polyester composition according to claim 1, characterized in that: The biodegradable polyesters include aliphatic polyesters and aliphatic-aromatic copolyesters.
6. The biodegradable polyester composition according to claim 5, characterized in that The aliphatic-aromatic copolyester comprises at least one aromatic dibasic acid selected from terephthalic acid and furandicarboxylic acid, at least one aliphatic dibasic acid selected from adipic acid, succinic acid, azelaic acid, sebacic acid and brassylic acid, and at least one diol selected from propylene glycol and butanediol, which are formed by polycondensation.
7. The biodegradable polyester composition according to claim 5, characterized in that The aliphatic polyester comprises polylactic acid, and the aliphatic polyester has a dextrorotatory monomer content of 1-15%.
8. The biodegradable polyester composition according to claim 1, characterized in that: The starch includes at least one of natural starch and natural starch derivatives.
9. The method for preparing the biodegradable polyester composition according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: weighing the dried raw materials, mixing them and sending them into a twin-screw extruder, extruding, drawing, cooling, pelletizing and drying to obtain a biodegradable polyester composition.
10. Use of the biodegradable polyester composition according to any one of claims 1 to 8 in the preparation of biodegradable film products.
Citation Information
Cited By
Biodegradable polyester composition, and preparation method therefor and use thereof
WO2026097974A1